4(p-6q)=0

Simple and best practice solution for 4(p-6q)=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4(p-6q)=0 equation:


Simplifying
4(p + -6q) = 0
(p * 4 + -6q * 4) = 0
(4p + -24q) = 0

Solving
4p + -24q = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '24q' to each side of the equation.
4p + -24q + 24q = 0 + 24q

Combine like terms: -24q + 24q = 0
4p + 0 = 0 + 24q
4p = 0 + 24q
Remove the zero:
4p = 24q

Divide each side by '4'.
p = 6q

Simplifying
p = 6q

See similar equations:

| -20=5(3x-10)-5x | | 118=8(1+7n)-2 | | 1/5x=x | | 8(3-5a)=-296 | | 7x^(2/3)-63=0 | | 3/7b=9 | | 14+c=39 | | 22/25X15/52X8/33 | | 8(3-5a)=-188 | | 5(-3x+5)=6-4x | | 27x-19-39x=-65 | | -3(2x+3)=6x+9 | | -0.1x+1.25=-0.5x+4.45 | | 8-9t=21r-17 | | (6+y)(2y+3)=0 | | 6p-16p=70 | | 3w+2-w=-3 | | 45x-21-17x=-63 | | 84=2k-5(2k-4) | | 3(x-1)+41=x-7(x+1) | | 6(4T+1)-13=T-(T+6) | | 6x+16=-2+8x | | 24x-81+7x=19 | | 25+10(12-x)=(2x-7) | | 84=-6(6+5x) | | 18^(1/3) | | 2.5/6=h/9 | | 8/12+9k/12=7/12 | | (2m+7)-(3-4m)=0 | | 2.5p-28=2p+26 | | y=5/4x+b | | 1.75m=21 |

Equations solver categories